The Application Value of the Central Lymph Node Metastasis Risk Assessment Model in Papillary Thyroid Microcarcinoma of Stage cN0: A Study of 828 Patients - Wang, Jinqiu; Sheng, Xianneng; Dai, Yongping; Zhang, Jiabo; Song, Lihua; Guo, Yu (Frontiers in Endocrinology, 2022)
Backgrounds: The aim of this study is to build a risk assessment system for central lymph node metastasis (CLNM) in papillary thyroid microcarcinoma (PTMC) of stage cN0, and to explore its application value in clinical practice. Methods: The clinic date of 500 patients of PTMC who underwent thyroid operation from 2013 to 2015 in Ningbo First Hospital were selected as the model group. Independent risk factors related to CLNM in PTMC were analyzed and determined, and a risk assessment system for CLNM was preliminarily established. Furthermore, the clinicopathological data from 328 PTMC patients with the same conditions as the model group from 2016 to 2017 were further collected as the validation group to verify the diagnostic value of the risk assessment system. Results: The risk assessment system was based on the score rating (score ≤ 5 was classified as low-risk, 6~8 as medium-risk, and ≥ 9 as high-risk). The area under receiver operating characteristic curve (ROC) was 0.687 (95% CI:0.635-0.783). According to the risk assessment system, 328 PTMC patients in the validation group were scored. Among the low-risk group, the moderate-risk group and the high-group, 96.8%, 58.1% and 43.2% were the CLNM (-) patients, and 3.1%, 41.9% and 65.8% were CLNM (+) patients respectively. The area under ROC was 0.837（95% CI:0.778-0.869）. Conclusions: The risk assessment system in this study is of diagnostic value and can provide a theoretical foundation for intraoperative decision-making of prophylactic central neck dissection (pCND).